Vitamin C intervention may lower the levels of persistent organic pollutants in blood of healthy women – A pilot study. (June 2016) - Guo, Weihong; Huen, Karen; Park, June-Soo; Petreas, Myrto; Crispo Smith, Sabrina; Block, Gladys; Holland, Nina
Abstract: Emerging evidence suggests that exposure to endocrine-disrupting chemicals including persistent organic pollutants (POPs) such as organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs) has a long term impact on human health. The goal of this pilot study was to test whether antioxidant intervention by vitamin C supplementation may be a remedial approach to decrease body burden of POPs in humans. Using solid phase extraction coupled with a triple quadrupole mass spectrometer and a gas chromatography high resolution mass spectrometry, we measured 18 PCBs, 7 OCPs, and 5 PBDEs in the blood of 15 healthy California women (8 were obese/overweight and 7 had normal weight) before and after 2 months of vitamin C supplementation (1000 mg/day). We observed higher PBDE levels than PCBs and OCPs, but only PCB and OCP levels were strongly and positively correlated with participant's BMI and age. We also found statistically significant decreases in 6 PCBs (PCB-74, PCB-118, PCB-138, PCB-153, PCB-180, and PCB-187), and 2 OCPs (4, 4′-DDE, and 4, 4′-DDT), but not PBDEs after vitamin C supplementation. Pending confirmation of this pilot finding in a larger study of both sexes, vitamin C intervention may have important public health implications in protecting health by reducing body burdens of POPs. Highlights: We measured POPs in the blood of 15 California women before and after 2-month vitamin C supplementation (1000 mg/day). We found that the levels of PCBs and OCPs, but not PBDEs were positively correlated with participant's BMI and age. We found statistically significant decreases in 6 PCBs and 2 OCPs but not PBDEs after vitamin C supplementation. Pending confirmation of this pilot finding in a larger study, vitamin C intervention may have public health implications.